Enhancing Students Critical Thinking Skills And Creativity In PJBL-Based Stem Approach To Biotechnology Online Practicum In Mipa Laboratory Iain Syekh Nurjati Cirebon - Sholikah, Maratus; Hindriana, Anna Fitri; Abidin, Zaenal (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2022)
The aim of this research is to enhance students' creativity and critical thinking skills after using a STEM approach with an online project-based practicum model on conventional Biotechnology courses. The research method uses quasi experimentation with the design of the pretest-posttest control group. The samples were randomly taken by 50 students, which was divided into experimental groups and control groups. Data collection techniques use critical thinking skills tests, questionnaires, implementation observations, performance observations and documentation.Data analysis techniques use descriptive analysis and average different tests. The conclusions of the study are: (1) The results showed a significant average difference in critical thinking skills between experimental classes and control classes after the implementation of STEM approach based on the PjBL model with classes that did not use the STEM approach based on the PjBL model in biotechnology courses in tadris Biology Department Semester 6 IAIN student Sheikh Nurjati Cirebon as evidenced by a probability value (p) of 0.015 < 0.05. (2) Creativity of students in the experimental class of the highest indicators on flexibility and original, while the lowest indicators are on the smoothness indicator